Role of parks in enhancing recreational behaviours among youth / Dwi Rizka Zulkia - Zulkia, Dwi Rizka (2015)
Youths require recreational activities to enhance their physical and mental health. This study seeks to identify the relationship between built environment factors, youths‘ recreational behaviours and obesity. This study was conducted to determine physical activity, sedentary behaviour, accessibility and safety of recreational parks, and their relationship with body weight status of youths. Methods: Respondents comprise of 200 youths, aged between 15 to 16 years old, from two (2) randomly selected senior high schools in Subang Jaya, Selangor. Physical activity and sedentary behaviours were measured by the Physical Activity Questionnaire for Adolescents (PAQ-A) and The Adolescent Sedentary Activity Questionnaire (ASAQ). Height and weight were measured to compute body mass index (BMI). Accessibility and safety of recreational parks were also assessed and observed. Results: The findings revealed that almost half of the respondents have a normal BMI, while 19.0% were severely thin, 16.0% were overweight and 9.0% were obese. Ninety percent of respondents have a park near their homes, about less than 0.5km, and most of the respondents went to the park by walking (89.5%). For physical activity, jogging is the best physical activity for both males and females on weekdays (73.0%). On weekends, males are more physically active than females. For sedentary behaviours, watching television is the best choice for respondents to spend their leisure time, about 96.0% on weekdays and 89.5% on weekends. There is a significant relationship between BMI and youths who prefer watching television, which means that as watching television increases, BMI increases. Lack of facilities at the park is the top reason for not going to the park and they do not feel safe in the park because fear of crimes. Conclusion: This study demonstrates the need of youths to be healthy and physically active by playing sports at the park as their recreational activities. Support in terms of proximity of the parks from their home, safety and the provision of the facilities affect their recreational activities.